Tetrodotoxin levels of three pufferfish species (Lagocephalus sp.) caught in the North-Eastern Mediterranean sea. (March 2019) - Kosker, Ali Rıza; Özogul, Fatih; Ayas, Deniz; Durmus, Mustafa; Ucar, Yılmaz; Regenstein, Joe M.; Özogul, Yesim
Abstract: Tetrodotoxin (TTX) levels in Lagocephalus sceleratus (Silverstripe blaasop), Lagocephalus spadiceus (Half-smooth golden pufferfish) and Lagocephalus suezensis (Suez puffer) caught in Mersin Bay in the Northeastern Mediterranean Sea were analysed using Q-TOF LC/MS. Pufferfish were caught using trawl fishing, longlining and fishing line from December 2015 to October 2016. The TTX changes in the gonads, livers, intestines, skins and muscle tissues were evaluated according to sex and season. TTX levels for L. sceleratus and L. suezensis for all tissues were in the range of 0.69–35.6 μg/g and 0.67–3.09 μg/g, respectively. The highest TTX levels were observed in the gonads of female L. sceleratus caught in the autumn, and in the skin of L. suezensis caught in the spring but no quantifiable levels of TTX were found for L. spadiceus . In conclusion, L. sceleratus and L. suezensis species caught in the North-Eastern Mediterranean are toxic, and their consumption is unsafe. Graphical abstract: Image 108 Highlights: Pufferfish are harmful species that have spread rapidly in the Mediterranean Sea recently. TTX contents in pufferfish were determined by using the Q-TOF LC/MS. This is the first report on the TTX content of L. suezensis and L. spadiceus in the Mediterranean Sea. Regardless of TTX levels, L. sceleratus and L. suezensis are highly toxic pufferfish that is dangerous for public health.